KEARIFAN LOKAL, MODAL SOSIAL DAN PEMBANGUNAN BERKELANJUTAN - Sagajoka, Estherlina; Fatima, Imaculata (ANALISIS, 2023)
This Research aims to examine and determine the relationship between local wisdom, social capital and sustainable development.  The  data  and  information used in  writing this  article comes from literature studies nd literature reviews of vrious  writings and  documents relevant to local  wisdom,  social capital and sustainable development. Both offline library documents written  online.  The  result of the study show that the  relationship between local wisdom (IndigenousKnoledge) and  social  capital with  sustainable  development  is that local   wisdom is the knowledge of local people wwho  hve lived in  place for a long time,  base on  values developed from  generation.  Social  capitl   is  wwht llows local  communities to  survive and develop sustainably base on  local  wisdom,  Where community knowledge in certain Fields (Economic Activities,  Social  activities and environmental adaption) is  beneficial   for the  surrounding  environment whilw maintaining environmental sustainability,  and has  been carried out for generations.  From  generations   to  generation.  Knowledge of  costoms and  social  capital  are important factors that have a significant impact on  community economic  growth and  sustainable   development. Although formal  reseach on  Indigenous Konwledge and social capital  is still scarce and currently under  development,  several preliminary studies on mutual cooperation and wwork institutions are very helpful for  rural communities, at leas opening  wider opportunities as the main benchmark for more intensive and in-depth reseach on  working practices and mechanisms as well as the sustainability of lokal  wisdom and  social  capital  in  Indonesia,  especially in  rural  areas.